Peer rejection in elementary school: A general outlook - García Bacete, Francisco-Juan; Sureda García, Inmaculada; Monjas Casares, María Inés (Anales de Psicología / Annals of Psychology, 2010)
In this paper we carry out a general approach to the study of peer rejection. After commenting the contributions of peer relations to the children’s development and giving examples of negative and unsatisfactory relationships, rejection is presented as an interpersonal process in which we can consider both the rejectee’s characteristics and the context in which rejection takes place. This process encloses a negative spiral that limits the opportunities of learning with serious negative consequences. The results obtained from various studies among primary education pupils in Castellon, Valladolid and Palma de Mallorca point out that the reasons given by children to reject their peers are many and varied, that the pro-portion of children identified as rejected is very high and stable through-out schooling (11.3%). The population of rejected pupils is very heteroge-neous, but they all have in common that their levels of sociability are significantly lower compared to others, that they are predominantly males (16% boys versus to 5.6% girls) and that they show high stability. Finally, in the context of the slim success displayed by interventions, we have designed some action principles and specific proposals of intervention and revised the new agenda.